08.01 Heat shock protein 90 is increased in muscle tissue and plasma in idiopathic inflammatory myopathies. (1st March 2017) - Storkanova, Hana; Krystufkova, Olga; Klein, Martin; Mann, Herman; Vernerova, Lucia; Spiritovic, Maja; Zamecnik, Josef; Pavelka, Karel; Senolt, Ladislav; Vencovsky, Jiri; Tomcik, Michal
Abstract : Background: Heat shock proteins (Hsps) are chaperones playing important roles in skeletal muscle physiology, adaptation to exercise or stress, and activation of inflammatory cells. The aim of our study was to assess Hsp90 expression in muscle biopsies and plasma of patients with idiopathic inflammatory myopathies (IIM) and to characterise its association with IIM-related features. Methods: Total of 277 patients with IIM (198 females, 79 males; mean age 54.8; disease duration 4.1 years; dermatomyositis (DM, 104)/polymyositis (PM, 104)/cancer associated myositis (CAM, 42)/necrotizing myopathy (IMNM, 27)) and 100 age-/sex-matched healthy individuals were included in plasma analysis and 50 muscle biopsy samples were stained for Hsp90 (in PM, DM, IMNM, myodystrophy, myasthenia gravis, 10 each). Plasma Hsp90 was measured by ELISA (eBioscience, Vienna). CK, LD, ALT, AST and CRP were analysed by routine techniques and IIM-specific autoantibodies by in-line blot/immunoprecipitation. Data are presented as median. Results: In muscle biopsies Hsp90 expression was higher in IIM than in myodystrophy (myasthenia gravis used as another control was negative). Increased Hsp90 was detected in perifascicular degenerating and/or regenerating fibres, inflammatory cells (DM, PM), and necrotic and regenerating fibres (IMNM). Plasma Hsp90 levels were increased in IIM patients compared to healthy controls (20.2 vs. 9.2 ng/ml, p<0.0001). Hsp90 levels in all patients positively correlated with LD (r=0.551, p<0.0001) and AST (r=0.372, p<0.0001). Increased Hsp90 was associated with decreased MMT8 values (r=−0.136, p=0.029), in particular in proximal muscles. Hsp90 positively correlated with patient and doctor disease activity (r=0.222, p=0.0004; r=0.217, p=0.0005, respectively), pulmonary (r=0.222, p=0.0004) and muscle disease activity (r=0.146, p=0.018), MITAX (r=0.175, p=0.005) and MYOACT (r=0.159, p=0.012), and with MDI extent/severity (r=0.215, p=0.003; r=0.120, p=0.041, respectively). Higher Hsp90 was found in patients with interstitial lung disease, cardiac involvement and dysphagia (25.4 vs. 18.9, p=0.004; 27.5 vs. 19.3, p=0.004; 25.0 vs. 18.2 ng/ml, p=0.018, respectively). Conclusions: We demonstrate increased Hsp90 expression in IIM muscle biopsy samples, specifically in inflammatory cells, degenerating, regenerating and/or necrotic fibres. Increased Hsp90 plasma levels in IIM patients are associated with disease activity and damage, and with the involvement of proximal skeletal muscles, heart and lungs. Acknowledgement: Supported by AZV-16–33542A.